Building Writing Skills in English in Fifth Graders: Analysis of Strategies Based on Literature and Creativity - Niño, Fernando López; Páez, Martha Elizabeth Varón (English language teaching (Toronto), 2018)
The present article is centered on the description and analysis of the process of action-research followed by a group of twenty eight fifth graders of primary level in a public school in Colombia who improved their writing ability in English as a Foreign Language through the application of several creativity writing strategies. Among those strategies we can count the use of acrostics, calligrams, comic strips and posters, connecting children with fiction and real information taken from subjects taught at school. This research was designed with the objective of developing writing skills in a creative way, based on qualitative and quantitative methods by using surveys, checklists, field notes and a final interview to collect data. Findings revealed that writing mistakes were diminished after each one of the sessions application. Additionally, children were motivated to write in English and to assume different positions about topics of their interest from the advantages provided from new knowledge acquired about diverse topics related to their lives.